Kin but less than kind: within-group male relatedness does not increase female fitness in seed beetles. Issue 1910 (11th September 2019) - Berg, Elena C.; Lind, Martin I.; Monahan, Shannon; Bricout, Sophie; Maklakov, Alexei A.
Abstract : Theory maintains within-group male relatedness can mediate sexual conflict by reducing male–male competition and collateral harm to females. We tested whether male relatedness can lessen female harm in the seed beetle Callosobruchus maculatus . Male relatedness did not influence female lifetime reproductive success or individual fitness across two different ecologically relevant scenarios of mating competition. However, male relatedness marginally improved female survival. Because male relatedness improved female survival in late life when C. maculatus females are no longer producing offspring, our results do not provide support for the role of within-group male relatedness in mediating sexual conflict. The fact that male relatedness improves the post-reproductive part of the female life cycle strongly suggests that the effect is non-adaptive. We discuss adaptive and non-adaptive mechanisms that could result in reduced female harm in this and previous studies, and suggest that cognitive error is a likely explanation.